Joshua - McConville, J. G. (J. Gordon); Williams, Stephen N. (Stephen Nantlais) (Grand Rapids, Mich. : W.B. Eerdmans Pub. Co., 2010)
"In this volume Gordon McConville and Stephen Williams interpret the book of Joshua in relation to Christian theology, providing exegetical commentary and reflection on an often-troubling book that nonetheless plays a key role in the biblical drama of salvation. McConville and Williams address significant theological themes in Joshua, such as land, covenant, law, miracle, judgment (including the problem of genocide), and idolatry. They posit that the theological topics engaged in Joshua are not limited to the horizons of the author and first readers of the book, but that this ancient text is part of a much larger testimony that concerns readers yet today." ""What a marvelous book! Many commentaries on Joshua are disappointing and dispiriting; after using them, you wonder what the point was. This one helps you understand the book, helps you see the point, and sets you thinking energetically and constructively on the theological issues it raises."---John Goldingay, Fuller Theological Seminary" ""In the light of Qoheleth's tired comment---'Of making many books there is no end'---one can be forgiven for asking whether we need yet another English commentary on the book of Joshua. Having had opportunity to dive into this new one coauthored by Old Testament scholar Gordon McConville and systematic theologian Stephen Williams, I can only respond with another of Qoheleth's sayings: `Two are better than one, for they have a good return for their labor.' This collaborative effort in theological exegesis is first-rate both as exegesis and as theological interpretation, brilliantly demonstrating the organic and necessary link between the two."---V. Philips Long, Regent College, Vancouver"--BOOK JACKET.
Introduction to Joshua / Gordon McConville -- Commentary on Joshua / Gordon McConville -- Theological horizons of Joshua. Theology in the book of Joshua / Stephen Williams -- Joshua and biblical theology / Gordon McConville -- A response to Gordon McConville / Stephen Williams -- Reading Joshua today / Stephen Williams -- A response to Stephen Williams / Gordon McConville.
Includes bibliographical references (p. 236-245) and indexes.
Keywords: Bible. -- Commentaries; Bible. -- Theology